Fertilizer subsidies and food self‐sufficiency in Indonesia. (8th January 2014) - Warr, Peter; Yusuf, Arief Anshory
Abstract Indonesia is a net importer of almost all of its staple foods. National self‐sufficiency in food, especially the main staple, rice, is a core objective of economic policy. Poverty reduction is also a core policy objective. Since the 1970s, Indonesia has used agricultural input subsidies, especially on fertilizer, to stimulate agricultural production, largely in pursuit of the goal of rice self‐sufficiency. More recently, it has also used output protection, especially in rice, for the same purpose. This article utilizes a multisectoral, multihousehold general equilibrium model of the Indonesian economy to study the trade‐offs between the goals of self‐sufficiency and poverty reduction when two alternative means are used to achieve them: a fertilizer subsidy, on the one hand, and output protection, on the other. It does this by analyzing the aggregate and distributional effects of these two sets of policies and by comparing their effects with nonintervention. The analysis shows that, in terms of its effects on poverty, a fertilizer subsidy can be a more effective instrument for achieving the goal of rice self‐sufficiency than final product import restrictions.